Transfusion and Risk of Infection in Canada: Update 2005 (Canadian Journal of Infectious Diseases and Medical Microbiology)
In Canada and other countries, many steps are taken to minimize the risk of infection through the transfusion of blood or blood products (1). However, the infection risk can never be zero because these are biological products that are taken from living donors who are never 'germ free' (2). This is in contrast to drugs that can be manufactured de novo under sterile conditions in a laboratory. The present note provides an update on transfusion infection risks in Canada. It replaces the 2004 note (3) and may be helpful to practitioners in discussions with patients and parents toward obtaining informed consent before blood or blood product administration.